Determinant of MSMEs Performance and its Impact on Province GRDP in Indonesia - Salim, M Noor; Susilastuti, Darwati; Rafiqah, Imas Wildan (International Journal of Business, Economics and Management, 2020)
The purpose of this study was to determine (1) the simultaneous and partial influence of soybean price, consumption of tofu tempeh, the exchange rate of the rupiah against the US dollar, and interest rates factors on MSMEs income, (2) dominant factors on tofu tempeh MSMEs income and (3) the effect of tofu tempeh MSMEs income on the Province GRDP. This research is a quantitative study with a purposive method of determining research areas and a quarterly time series secondary data analysis method from 2009-2019 using OLS Multiple Regression. The analysis shows that all variables simultaneously have a significant effect on MSME income. Partially, the variables that have a significant positive effect on the income of tofu tempeh MSME are soybean prices, consumption of tofu tempeh and the exchange rate, while interest rates have a negative effect. The coefficient of determination of 96% with the magnitude of the determinant partially from the largest in the sequence is the consumption of tofu tempeh, soybean prices, exchange rates, and interest rates, there is no dominant factor. MSMEs income proxy with recursive income has a significant positive effect on Provincial GRDP with a determinant coefficient of 55%. The research findings are that MSMEs are resistant to fluctuations in exchange rates and contribute greatly to the GDRP.